2021
DOI: 10.1101/2021.10.27.21265329
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using machine learning to improve diagnostic assessment of ASD in the light of specific differential diagnosis

Abstract: BackgroundDiagnostic assessment of ASD requires substantial clinical experience and is particular difficult in the context of other disorders with behavioral symptoms in the domain of social interaction and communication. Observation measures such as the Autism Diagnostic Observation Schedule (ADOS) do not take into account such comorbid and differential disorders.MethodWe used a well-characterized clinical sample of individuals (n=1262) that had received detailed outpatient evaluation for the presence of an A… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 57 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…Based on the present data, it can be suggested that going through the short DT pathways, to reinsure the decision for or against ASD, may decrease the risk of false positives and false negatives in individuals with below and above average IQ levels remarkably. However, it is relevant to keep in mind that, in addition to or in interaction with IQ, further factors may influence the complex diagnostic process, including other differential or comorbid diagnoses ( 17 , 18 , 36 , 45 ), female gender ( 46 ), parental psychiatric diagnoses ( 47 ), aspects of healthcare supply ( 48 , 49 ), and experience of the diagnostician ( 50 ). Further, since IQ and language are observed to account for the heterogeneity in ASD and the variability in diagnostic and therapeutically outcomes, it appears relevant to consider also developmental trajectories of autistic symptom severity and adaptive functioning ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the present data, it can be suggested that going through the short DT pathways, to reinsure the decision for or against ASD, may decrease the risk of false positives and false negatives in individuals with below and above average IQ levels remarkably. However, it is relevant to keep in mind that, in addition to or in interaction with IQ, further factors may influence the complex diagnostic process, including other differential or comorbid diagnoses ( 17 , 18 , 36 , 45 ), female gender ( 46 ), parental psychiatric diagnoses ( 47 ), aspects of healthcare supply ( 48 , 49 ), and experience of the diagnostician ( 50 ). Further, since IQ and language are observed to account for the heterogeneity in ASD and the variability in diagnostic and therapeutically outcomes, it appears relevant to consider also developmental trajectories of autistic symptom severity and adaptive functioning ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…MAPS may be superior to screening tools as they are able to integrate information from multiple sources and weigh its significance for an individual. This is reflective of the clinical challenges in making sense of complex presentations where clinician experience and skill is required to integrate the data from assessment tools together with the clinical assessment in a nuanced manner to arrive at a diagnostic formulation which avoids diagnostic overshadowing and accounts for comorbidity and contributing bio-psychosocial context 13,14 .…”
Section: Discussionmentioning
confidence: 99%
“…This variability limits the clinical usefulness of categorical diagnostic models in complex presentations with multiple comorbidities [8][9][10][11] as their symptom profile may be non-specific to a particular diagnosis at the time of presentation. Additionally, psychometric tests may lead to false positives in complex cases, or, they also produce non-specific findings which are difficult to integrate into a formulation for an individual [12][13][14][15][16] . Experienced clinicians intuitively weight the data obtained from psychometric tools such as cognitive testing and autism assessment tools depending on the co-morbidities present.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, as the symptom profiles of the different classes demonstrate overlapping but also different profiles, the hybrid model appears more suitable for the early detection of ASD cases and may help to differentiate ASD from other mental disorders compared to a purely dimensional approach. Taking the symptom profiles into account could for example improve diagnostic accuracy [67].…”
Section: Discussionmentioning
confidence: 99%